Crop metabolomics : from diagnostics to assisted breeding - Alseekh, Saleh; Bermudez Salazar, Luisa; De Haro, Luis Alejandro; Fernie, Alisdair R.; Carrari, Fernando (Springer, 2019)
Background Until recently, plant metabolomics have provided a deep understanding on the metabolic regulation in individual plants as experimental units. The application of these techniques to agricultural systems subjected to more complex interactions is a step towards the implementation of translational metabolomics in crop breeding. Aim of Review We present here a review paper discussing advances in the knowledge reached in the last years derived from the application of metabolomic techniques that evolved from biomarker discovery to improve crop yield and quality. Key Scientific Concepts of Review Translational metabolomics applied to crop breeding programs.